Relationship between plasma lipids and mild cognitive impairment in the elderly Chinese: a case-control study - He, Qian; Li, Qing; Zhao, Jiangang; Wu, Tianfeng; Ji, Lu; Huang, Guowei; Ma, Fei (Lipids in health and disease, 2016)
High lipid levels may constitute a more important risk factor for cognitive health in previous studies. However, the association of plasma lipids with mild cognitive impairment (MCI) among elderly people had not been studied exactly. This study aims to explore the relationship between plasma lipids/lipoproteins and the risk of MCI in elderly Chinese individuals. CSI-MCI study was a preliminary case-control study of the association of plasma lipids/lipoproteins with MCI in 112 MCI cases and 115 cognitively normal controls. Plasma total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), and triglycerides (TG) levels were measured in fasting blood samples. Multivariable logistic regression was used to evaluate the potential association between MCI and these factors. Statistical models were adjusted for multiple demographic and biological covariates. The subjects with MCI were significantly older, higher percentage of females and less educated than controls (P <0.05). As expected, subjects with MCI had lower MMSE score compared with controls (P <0.05). Multivariate logistic regression analysis showed that higher plasma TC level was associated with the risk of MCI in models adjusting for age, sex and education. However, This association was attenuated after adjusting for BMI, Type 2 diabetes mellitus, heart disease and hypertension. Plasma TG level was negatively associated with the risk of MCI. The adjusted odds ratio (OR) of MCI was significantly reduced for the highest quartile of plasma TG level (OR: 0.76, 95 % CI: 0.48-0.97), but not for the second or third quartile, compared with the lowest quartile (adjusted models). Plasma HDL level was significantly negatively associated with the risk of MCI. There was no association between plasma LDL level and the risk of MCI, adjustment for demographics, vascular disorders did not change this relation. Plasma TC was significantly higher in MCI subjects compared to cognitively normal controls, Elevated plasma HDL and triglyceride were associated with the occurrence of MCI. These findings need to be confirmed in further longitudinal studies.